2008
DOI: 10.1029/2007jc004528
|View full text |Cite
|
Sign up to set email alerts
|

High gas‐transfer velocity in coastal regions with high energy‐dissipation rates

Abstract: [1] We measured the gas-transfer velocity (k) and analyzed factors regulating k at coral reefs and an estuary at Ishigaki Island, Japan, using the floating-chamber method and the measured energy-dissipation rate (e) to represent turbulence in a small-eddy model. We confirmed the validity of the floating-chamber method quantitatively for the first time by the comparing e values inside and outside the chamber device. We also compared k to e and empirical parameters such as wind and current speeds. Measured k had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
56
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 49 publications
9
56
1
Order By: Relevance
“…Zappa et al (2007) found a good relationship when combining data from four different systems (rivers to estuaries). Similar results were obtained in a recent study (Tokoro et al 2008) in marine coastal systems that used the FC method. However, some difference appears between the slopes of these relationships.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Zappa et al (2007) found a good relationship when combining data from four different systems (rivers to estuaries). Similar results were obtained in a recent study (Tokoro et al 2008) in marine coastal systems that used the FC method. However, some difference appears between the slopes of these relationships.…”
Section: Discussionsupporting
confidence: 78%
“…These values are comparable to those of the upper mixed layer of other lakes (MacIntyre et al 1995) but lower than dissipation rates found under breaking wave conditions (Terray et al 1996), in estuaries with tidal currents (Zappa et al 2007), or in the turbulent coastal environment (Tokoro et al 2008). TKE dissipation rate inside the FC (e in ) averaged 1.5 3 10 24 6 1.1 3 10 24 m 2 s 23 (mean 6 SE, n 5 49) at the ER site and 1.1 3 10 24 6 9.6 3 10 25 m 2 s 23 (mean 6 SE, n 5 9) in ET lakes (Table 1).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations